LPS inmobilization on porous and non-porous supports as an approach for the isolation of anti-LPS host-defense peptides - Lopez-Abarrategui, Carlos; Martinez, Alberto; Reyes-Acosta, Osvaldo; Franco, Octavio L.; Otero-González, Anselmo J. (Frontiers in Microbiology, 2013)
Lipopolysaccharides (LPS) are the major molecular component of the outer membrane of Gram-negative bacteria. This molecule is recognized as a sign of bacterial infection, responsible for the development of local inflammatory response and, in extreme cases, septic shock. Unfortunately, despite substantial advances in the pathophysiology of sepsis, there is no efficacious therapy against this syndrome yet. As a consequence, septic shock syndrome continues to increase, reaching mortality rates over 50% in some cases. Even though many preclinical studies and clinical trials have been conducted, there is no FDA-approved drug yet that interacts directly against LPS. Cationic host defense peptides could be an alternative solution since they possess both antimicrobial and antiseptic properties. Host defense peptides are small, positively charged peptides which are evolutionarily conserved components of the innate immune response. In fact, binding to diverse chemotypes of LPS and inhibition of LPS-induced pro-inflammatory cytokines from macrophages have been demonstrated for different host defense peptides (HDPs). Curiously, none of them have been isolated by their affinity to LPS. A diversity of supports could be useful for such biological interaction and suitable for isolating host defense peptides that recognize LPS. This approach could expand the rational search for anti-LPS host defense peptides.